2017
DOI: 10.1002/jctb.5365
|View full text |Cite
|
Sign up to set email alerts
|

Salting‐out extraction of bio‐based isobutanol from an aqueous solution

Abstract: BACKGROUND More efficient downstream separation technologies need to be explored due to the low concentration of bio‐based isobutanol in the fermentation broth. The salting‐out extraction of isobutanol from its aqueous solution by employing nine salts (K4P2O7·3H2O, K2HPO4·3H2O, K3PO4·3H2O, K2CO3, K2SO4, KCl, Na2CO3, Na2SO4, NaCl) as salting‐out agents and three organic solvents (2‐ethyl‐1‐hexanol, cyclopentanol, 2‐methyl‐2‐butanol) as extractants were investigated at 298.15 K. RESULTS The recovery was greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…When the initial salt concentration of K 2 CO 3 is 350 g/kg, all isobutanol in the aqueous phase can be extracted into the organic phase, and the recovery of isobutanol is as high as 100%. When K 2 CO 3 is used as the salting‐out agent, and the recovery rate of isobutanol is 100%, the amount of the salting‐out agent used in the salting‐out method is a little higher than that of the salting‐out extraction method (250 g/kg) [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the initial salt concentration of K 2 CO 3 is 350 g/kg, all isobutanol in the aqueous phase can be extracted into the organic phase, and the recovery of isobutanol is as high as 100%. When K 2 CO 3 is used as the salting‐out agent, and the recovery rate of isobutanol is 100%, the amount of the salting‐out agent used in the salting‐out method is a little higher than that of the salting‐out extraction method (250 g/kg) [40].…”
Section: Resultsmentioning
confidence: 99%
“…[26, 3439] In the previous study, the effects of extractant types, concentration and extraction temperature on the extraction efficiency of isobutanol from aqueous solutions were studied when cyclopentanol, tert‐pentanol, n‐valeraldehyde and isooctyl alcohol were used as extractants. [28] The salting‐out extraction of isobutanol from aqueous solutions was also investigated by employing nine salts (K 4 P 2 O 7 ·3H 2 O, K 2 HPO 4 ·3H 2 O, K 3 PO 4 ·3H 2 O, K 2 CO 3 , K 2 SO 4 , KCl, Na 2 CO 3 , Na 2 SO 4 , NaCl) as salting‐out agents and three organic solvents (2‐ethyl‐1‐hexanol, cyclopentanol, 2‐methyl‐2‐butanol) as extractants at 298.15 K [40]. Higher recovery of isobutanol and dehydration ratio was achieved simultaneously with the K 2 CO 3 as the salting‐out agent.…”
Section: Introductionmentioning
confidence: 99%
“…Among different extractants 2-ethyl 1 hexanol served as best host. Isobutanol recovery of 100% was achieved by this method [ 55 ].…”
Section: Current Isobutanol Production Strategies Using Microorganismsmentioning
confidence: 99%
“…The four salting‐out agents that have achieved phase separation for ethanol aqueous solution and the salting‐out effects are arranged in the order: K 4 P 2 O 7 > K 3 PO 4 > K 2 HPO 4 > K 2 CO 3 . In the study of salting‐out agents on the separation of the isobutanol + water system, it was found that potassium pyrophosphate (K 4 P 2 O 7 ) had the best phase separation ability among these salts . Therefore, K 4 P 2 O 7 was expected to recover IBE from the fermentation broth.…”
Section: Introductionmentioning
confidence: 99%
“…17 In the study of salting-out agents on the separation of the isobutanol + water system, it was found that potassium pyrophosphate (K 4 P 2 O 7 ) had the best phase separation ability among these salts. 18 Therefore, K 4 P 2 O 7 was expected to recover IBE from the fermentation broth.…”
Section: Introductionmentioning
confidence: 99%